DISTRIBUSI RATA-RATA PENGARUH ARTIFICIAL INTELLIGENCE TERHADAP KEMAMPUAN BERPIKIR KRITIS MAHASISWA - Aditya Nafil, Adam; Faris Jatmiko; Rizal Wahyu Saputra; Jadiaman Parhusip (LPPM Politeknik Pratama Kendal, 2024)
The use of artificial intelligence (AI) in education is increasingly widespread, particularly among students, to support learning processes. This study aims to analyze the impact of AI usage on students' critical thinking skills. The methods employed include qualitative interviews and observations, as well as quantitative surveys. The findings reveal that AI enhances learning efficiency and access to information; however, excessive reliance on AI may reduce students' independence and critical thinking abilities. While most students find AI features helpful in understanding material, such dependence diminishes efforts in reflection and independent analysis. The study highlights the importance of blending AI usage with the development of independent cognitive skills to maximize technological benefits without compromising critical thinking capabilities.